2007
DOI: 10.1073/pnas.0608274104
|View full text |Cite
|
Sign up to set email alerts
|

A silent chemokine receptor regulates steady-state leukocyte homing in vivo

Abstract: The location of leukocytes in different microenvironments is intimately connected to their function and, in the case of leukocyte precursors, to the executed differentiation and maturation program. Leukocyte migration within lymphoid organs has been shown to be mediated by constitutively expressed chemokines, but how the bioavailability of these homeostatic chemokines is regulated remains unknown. Here, we report in vivo evidence for the role of a nonsignaling chemokine receptor in the migration of leukocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
146
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(165 citation statements)
references
References 35 publications
9
146
3
1
Order By: Relevance
“…Moreover, CCR7 and CCR9 have been shown to play a role in various cancers (9). CCX-CKR scavenges CCL19 and CCL21 both in vitro and in vivo, thereby decreasing the free concentration of these chemokines (7,8,10). Indeed, low CCX-CKR expression levels in breast cancer tumor cells were correlated with an increase in lymph node metastasis and consequently poor survival rate of patients (11).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, CCR7 and CCR9 have been shown to play a role in various cancers (9). CCX-CKR scavenges CCL19 and CCL21 both in vitro and in vivo, thereby decreasing the free concentration of these chemokines (7,8,10). Indeed, low CCX-CKR expression levels in breast cancer tumor cells were correlated with an increase in lymph node metastasis and consequently poor survival rate of patients (11).…”
mentioning
confidence: 98%
“…CCL25, on the other hand, recruits antigen-experienced lymphocytes to the small intestine by activating CCR9 (6). Mouse CCX-CKR knock-out models demonstrated that CCX-CKR is important for steady-state homing of dendritic cells to skin-draining lymph nodes, T cell differentiation, and immune response kinetics in an experimental autoimmune encephalomyelitis model, by regulating local chemokine levels (7,8). Moreover, CCR7 and CCR9 have been shown to play a role in various cancers (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the thymus, CCRL1 is abundant in cTECs but not mTECs or thymocytes [20]. In fetal mice, CCRL1 regulates the migration of thymocyte precursors before vascularization [19]. It has been reported that CCRL1 deficiency results in thymus enlargement in adult mice, in association with altered thymocyte development and autoimmunity [21].…”
mentioning
confidence: 99%
“…To do so, Ribeiro et al [18] analyze the expression of the atypical chemokine receptor CCRL1 during mouse ontogeny. It is known that CCRL1 (previously known as CCX-CKR or CCR11) is a nonsignaling scavenger receptor for the CC chemokine ligands CCL19, CCL21, and CCL25 [19]. In the thymus, CCRL1 is abundant in cTECs but not mTECs or thymocytes [20].…”
mentioning
confidence: 99%